Action moyennable d'un groupe localement compact sur une algèbre de von Neumann II. - Anantharaman-Delaroche, Claire (Mathematica Scandinavica, 1982)
This is the continuation of our previous work on amenable actions of a locally compact group G on a von Neumann algebra M. We study stability properties of this notion of amenable action by extension and restriction. Wealso prove that an action of G on M is amenable if and only if the corresponding action of G on the centre Z(M) is amenable. Then we give applications to the study of injectivity of crossed products.